PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN IBU TENTANG ASI EKSKLUSIF DI WILAYAH KERJA UPTD PUSKESMAS LONG LOREH - Libut, Mayti; Citra, Nur; Febrianti, Selvia (Jurnal Kesehatan dan Pembangunan, 2025)
Health education and health promotion are forms of intervention or effort taht aim to influence behavior in a way that is conducive to health. Eksclusive breastfeeding is the provision of breast milk, without any additional food to infants from 0 to 6 months af age. The factors that influence exclusive breastfeeding are maternal knowledge and attitude. The Indonesian Health Profile for 2019 indicates that exclusive breastfeeding coverage in indonesia for six months was 50%, falling short of the Indonesian Ministry of Health’s target of 80 %. The purpose of the research was to determine the correlation between health education and mothers’ knowledge about exclusive breastfeeding in the catchment area of UPTD the Public Health Center of Long Loreh in 2024. The researcher employed quantitative research with a quasi-experimental approach, utilizing a one-group pretest-posttest design. The research sample consisted of 55 mothers who were either breastfeeding of had babies in the catchment area of the Public Health Center of Long Loreh. The sampling technique employed was total sampling. The data analysis technique employed was the chi-square test ( The results of the univariate analysis show that prior to health education, knowledge was classified as either good (27,3%), sufficient (50,9%) or less good (21,8%). Following health education, the proportion of individuals with good knowledge increased to 72,7 %, while the proportion with sufficient knowledge decreased to 27,3 %. Based on the chi square statistical test, the results obtained a p-value of 0,004 (p<0,05), indicating a statistically significant relationship between health education and maternal knowledge about exclusive breastfeeding. This result rejects the null hypothesis (H0) and accepts the alternative hypothesis (Ha). It concluded that health education can be done to mothers in every posyandu to enhance the knowledge and foster a positive attitude towards exclusive breastfeeding of infants aged 0-6 months.